Effects of combined exercise on salivary oxidative stress in hypertensive and normotensive postmenopausal women - Amaral, Ana Luiza; Mariano, Igor Moraes; Giolo, Jéssica Sanjulião; Dechichi, Juliene Gonçalves Costa; de Souza, Adriele Vieira; Batista, Jaqueline Pontes; de Souza, Tállita Cristina Ferreira; Caixeta, Douglas Carvalho; Peixoto, Leonardo Gomes; Teixeira, Renata Roland; Espindola, Foued Salmen; Puga, Guilherme Morais; et al. (FapUNIFESP (SciELO), 2022)
Aim: This study evaluated the effects of 10 weeks of combined exercise training on the salivary oxidative profile of hypertensive and normotensive postmenopausal women. Methods: Twenty-six non-obese postmenopausal women were divided into two groups: the hypertensive group (HT; n = 13; 58.9 ± 3.9 years; and BMI of 27.7 ± 4.6 kg/m2) or the normotensive group (NT; n = 13; 52.7 ± 5.2 years; and BMI of 26.9 ± 2.9 kg/m2). They performed 30 sessions of combined exercises over 10 weeks: 45 min per session, three times a week. Resting saliva samples were collected after an overnight fast to evaluate salivary nitrite levels and oxidative stress markers before and after training. Results: Two-way ANOVA showed that there was no difference in the responses over time between the hypertensive and normotensive groups in catalase, superoxide dismutase salivary activity, total antioxidant capacity, or lipid peroxidation. However, superoxide dismutase activity (ΔHT -0.87 ± 14.53 SOD/mg protein; ΔNT: 7.13 ± 9.39 SOD/mg protein; p < 0.01) and nitrite levels (ΔHT 10.32 ± 60.83 mM; ΔNT 101.92 ± 149.57 mM; p = 0.03) were higher overall in the hypertensive group compared to the normotensive group. Moreover, salivary nitrite levels increased over time (p = 0.04) in both groups. Conclusion: 10 weeks of combined exercise training did not change salivary oxidative stress markers in either normotensive or hypertensive postmenopausal women, although, after exercise training, nitrite levels increased in both groups, even with higher baseline salivary nitrite levels in hypertensive women. Thus, recurrent exercise seems to be a safe strategy after menopause from the standpoint of oxidative stress, regardless of the presence of hypertension.
Keywords: Climacteric; Combined exercise; Nitrite; Saliva; Superoxide dismutase